Cinema and popular music, a multifold relationship. The cases ofEnnio Morricone and David Lynch - Martinelli, Dario (Interdisciplinary Studies in Musicology, 2018)
The aim of this article is to discuss the complexity of the relationship between popular music and cinema. Since its very birth, cinema has established a solid collaboration with music. When films had no sound, music (back then played live) had the crucial role of creating moods, underlining specific sequences, and in general making speech not too missed. When sound appeared, musicals became immediately a dominant genre (and a rich source for business: cinema halls themselves, but also music-sheets and recordings). Shortly after, the subtle art of film music developed, granting — to film and music histories alike — some of the finest composers of the whole 20th century (Bernard Hermann, Nino Rota, John Williams, Ennio Morricone...), or allowing great composers and musicians in their own right, to deliver some of their best works in form of soundtrack (Miles Davis” Lift to the Scaffold or Duke Ellington’s Anatomy of a Murder, just to focus on jazz only). Whether film music must be considered a form of ’serious“ or ’popular' music is still source of debate, and definitely not in the scopes of the present essay. Instead, the point I wish to make here is that, regardless of its nature, the interaction between cinema and popular music is made of literally dozens of possible combinations, making this relationship one of the most interesting among the many existing within an art, cinema, which makes of multimediality and multimodality its primary strength (let alone identity: up to the point that a good portion of the early years of film studies were spent in deciding whether, after all, cinema could be considered an art of its own, or simply a combination of pre-existing arts). The analysis will proceed in a rather linear manner, by simply taking two case-studies: Ennio Morricone, a most celebrated film composer, and David Lynch, a cult-director who has established a strong bond with popular music in his cinematography. Perhaps unexpectedly, the case of Morricone will be only in part employed to discuss his scores for the likes of Leone or Pasolini: more attention will bedevoted to his not-so-well known (at least outside Italy) activity as pop songwriter and arranger. When it comes to Lynch, instead, the analysis will try to cover more or less all his interests in popular music, including his long-lasting professional collaboration (and personal friendship) with composer Angelo Badalamenti.